Characterization, high production and antimicrobial activity of exopolysaccharides from Lactococcus lactis F-mou. (July 2019) - Nehal, Fatima; Sahnoun, Mouna; Smaoui, Slim; Jaouadi, Bassem; Bejar, Samir; Mohammed, Sebaihia
Abstract: A new exopolysaccharide (EPS) was produced by the Lactococcus lactis F-mou strain (LT898177.1) isolated from the Sahrawi camel milk in the Bir-Naam region, Algeria. The most influential production parameters were screened by the Plackett-Burman design for enhancing EPS yield utilizing the Mech-Degla juice as a low-cost raw material. An optimum condition of a 0.49 of inoculum size, a 100 rpm of agitation rate, and a 12 h of incubation period resulted in a 301 g/L. This yield was 47 times higher than the one attained before the application of the Box-Behnken Design. Additionally, the FTIR analysis of the EPS confirmed the presence of hydroxyl, carboxyl, amide and sulphate groups. Furthermore, the SEM image showed a porous structure characterized by a flake-like basic configuration with an extremely dense assembly. The NMR studies indicated that EPS contained a backbone of→4-α-D-galactopyranose-(1→, →4, 6-α-D-glucopyranose-(1→, →6- α -D- galactopyranose -(1→ linkages plus a levan part. The EPS exhibited good water and oil holding capacities, a high antioxidant efficiency, and an excellent anti-clotting activity. EPS also showed a strong inhibitory activity against Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Listeria monocytogenes, Bacillus cereus, Proteus mirabilis, Acinetobacter baumannii, Enterobacter cloacae, and Candida albicans . Overall, the mentioned findings indicated that EPS could be utilized as a natural additive in pharmaceutical, food, and cosmetic industries. Highlights: Lactococcus lactis F-mou strain produced a new EPS. EPS was a branched heteropolysaccharide. EPS was a mix of galactoglucan and levan parts. High EPS economic production of 301 g/L was obtained.